CTNI-17. A MULTI-INSTITUTIONAL RANDOMIZED CLINICAL TRIAL COMPARING ASSAY - GUIDED CHEMOTHERAPY WITH PHYSICIAN-CHOICE TREATMENT FOR RECURRENT HIGH-GRADE GLIOMA (NCT03632135). (14th November 2022) - Ranjan, Tulika; Sengupta, Soma; Glantz, Michael; Green, Richard; Yu, Alexander; Aregawi, Dawit; Chaudary, Rekha; Chen, Ricky; Zuccarello, Mario; Lu-Emerson, Christine; Moulding, Hugh; Belman, Neil; et al.
Abstract: The presence of therapy-resistant cancer stem cells (CSCs) in recurrent high-grade glioma (HGG) patients contributes to poor clinical outcomes. The ChemoID functional anti-cancer assay targets cancer stem cells along with the bulk of the tumor cells. This trial aims to determine if ChemoID assay-guided treatment improves survival rates for recurrent HGG patients compared to the empirically physician-selected treatment. Patients with grade-III/IV recurrent glioma who failed standard of care (SOC) therapy were randomized (1:1) between two intervention groups. They received one of fourteen mono or combination chemotherapies based on the ChemoID assay or physician choice. The study met the primary outcome in the first interim analysis of 50 patients as per protocol. The ChemoID group had an improved survival rate (vs physician-choice). Median OS (mOS) was 12.5 months in the ChemoID group (95% CI, 10.2-14.7) vs 9 months in the physician-choice (95% CI, 4.2-13.8; log-rank P = .010). Mortality risk was lower in the ChemoID group (HR = 0.44; 95% CI, 0.24-0.81; P = .008). Median progression-free survival was 10.1 months in the ChemoID group vs 3.5 months in the physician choice (95% CI, 4.8-15.4 vs 1.9-5.1; log-rank < 0.001). Risk of progression was lower in the ChemoID group (HR = 0.25; 95% CI, 0.14-0.44; P < 0.001). The intention to treat (ITT) analysis of 78 patients showed substantially improved OS. The ChemoID group had a statistically significant longer median survival of 4.5 months. mOS was 12.0 months in the ChemoID group (95% CI, 10.8-13.2) vs 7.5 in the physician-choice group (95% CI, 3.5-11.5; log-rank P = .009). The ChemoID group had a decreased mortality risk (HR = 0.52; 95% CI, 0.24-0.81; P = .008). Compared with the physician-choice, the ChemoID group had a significantly longer OS in the ITT population. Our findings support that screening standard cytotoxic chemotherapies with a patient-specific anti-cancer assay improves survival outcomes in recurrent HGG patients.